Gender and ethnicity: The role of successful women in promoting equality and social change - Ferreira, R. A.; Santos, M. H. (Social Sciences, 2022)
This article analyzes the experiences and strategies of white and black women in positions of some power, in which they are able to strive to reduce inequalities and promote social change. From a qualitative perspective, this seeks to open the discussions around the possible applications of intersectionality between gender and “race”/ethnicity for studying the “tokenism phenomenon”. The results reveal six major themes that demonstrate how, while both white and black women share negative consequences of tokenism, the intersections of gender and “race”/ethnicity create dynamics that make black women’s experiences unique. Overall, we may therefore conclude the interviewees represent “agents of change” and deploy their power to promote equality in a variety of ways.